2019
DOI: 10.1002/adfm.201808119
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Molecules “Bridge”: Functional Ligand toward Highly Efficient and Long‐Term Stable Perovskite Solar Cell

Abstract: Interfacial ligand passivation engineering has recently been recognized as a promising avenue, contributing simultaneously to the optoelectronic characteristics and moisture/operation tolerance of perovskite solar cells. To further achieve a win-win situation of both performance and stability, an innovative conjugated aniline modifier (3-phenyl-2-propen-1-amine; PPEA) is explored to moderately tailor organolead halide perovskites films. Here, the conjugated PPEA presents both "quasi-coplanar" rigid geometrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 49 publications
3
107
0
Order By: Relevance
“…As a first consistency check, we compared the material candidates in figures 3(a) and b to materials that have already been used as transport or mesoporous scaffold layers in PSCs. We found that our search is consistent with common materials such as: NiO [25,52] and PbO [53,54] as intrinsic HTMs in PSCs, as well as ZnO [52] and TiO 2 [38] as electron-transporting materials (ETMs). Similarly, our candidate materials included ZrO 2 [39] and Al O 2 3 [55] which are used as mesoporous scaffolds in PSCs.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…As a first consistency check, we compared the material candidates in figures 3(a) and b to materials that have already been used as transport or mesoporous scaffold layers in PSCs. We found that our search is consistent with common materials such as: NiO [25,52] and PbO [53,54] as intrinsic HTMs in PSCs, as well as ZnO [52] and TiO 2 [38] as electron-transporting materials (ETMs). Similarly, our candidate materials included ZrO 2 [39] and Al O 2 3 [55] which are used as mesoporous scaffolds in PSCs.…”
Section: Resultssupporting
confidence: 79%
“…With increasing exposure to any of these destabilizing factors, the structure of the hybrid perovskite degrades and the PCE reduces concomitantly after several days or even hours [15,16]. Among the solutions that have been proposed to solve this stability and longevity problem are protective coating [17][18][19], the use of two-dimensional perovskites [20][21][22][23][24][25], and doping with small ions [14,[26][27][28][29][30]. Protective coating is particularly promising, as it can passivate the surface dangling bonds of the perovskite photoabsorber [31] and insulate the perovskite from heat and small molecules from the environment [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The research of a thin‐film photovoltaic device based on a hybrid organic–inorganic lead (Pb) halide perovskite material has been significantly progressed during the last decade, and the world record power conversion efficiency (PCE) has recently reached 24.2% . The promising performance of perovskite solar cells (PSCs) is already competitive with CdTe and polycrystalline silicon‐based solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been adopted to control defect density to improve the optical and electrical properties. For instance, various solution‐processing techniques, such as introducing organic small molecular, conjugated molecule materials, or ionic liquid additives, etc., have been used to regulate the crystal process to improve perovskite crystal quality and reduce defects/traps . Different kinds of passivation methods and passivating agents have also been reported to be capable of effectively passivating perovskite materials .…”
Section: Introductionmentioning
confidence: 99%